Overview of the Knowledge Level of Ninth-Grade female Students Regarding the Prevention of Anemia at SMP Putri Cahaya Medan - Rusmauli Lumban Gaol; Gryytha Tondang; Amando Sinaga; Meilin Angelia Simarmata (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Anemia is a medical condition characterized by a lower-than-normal number of red blood cells or hemoglobin levels in the blood. This results in a reduced ability of the blood to carry oxygen throughout the body. Consequently, individuals with anemia may experience various symptoms such as fatigue, dizziness, and shortness of breath. The main causes of anemia are generally due to a lack of knowledge about this condition and deficiencies in nutrients such as iron.The purpose of this study is to determine the level of knowledge among ninth-grade female students regarding the prevention of anemia and their ability to prevent it. This study uses a descriptive research method, focusing on describing the level of knowledge of ninth-grade female students about the prevention of anemia.The study uses the Total Sampling method as the sampling technique, which means that all members of the population are included as respondents. Therefore, the number of respondents in this study is equal to the total population of female students, which are 54 individuals. Data collection is conducted using a closed-ended questionnaire consisting of 20 items covering indicators such as the definition of anemia, its etiology, signs and symptoms, treatment, and prevention.The results of the study show that knowledge regarding the definition of anemia is in the good category for 35 respondents (64.8%), knowledge about etiology is in the fair category for 35 respondents (64.8%), knowledge of signs and symptoms was in the fair category for 45 respondents (83.3%), knowledge about treatment is in the good category for 33 respondents (61.1%), and knowledge of prevention is in the fair category for 32 respondents (59.3%).It is hoped that by increasing the knowledge of ninth-grade female students about the prevention of anemia, schools and health workers can work together to carry out regular health education.